A new species of deathwatch beetle (Coleoptera: Anobiidae) discovered in Europe - Büche, Boris; Lundberg, Stig (Entomologica Fennica, 2002)
A new species of the genus Dorcatoma Herbst (Coleoptera: Anobiidae) is described based on material from Latvia and Sweden, and recorded also for Poland. Dorcatoma janssoni n. sp. is very close in appearance to D. chrysomelina Sturm, but male genitalia and biology are different. Antennae and male and female genitalia are figured, and the biology of the new species is described. Dorcatoma ambjoerni Baranowski is removed from the synonymy of D. setosella Mulsant & Rey. A key is provided for the European species of the Dorcatoma chrysomelina-group.